Calculating equation of the curve.
(y-12) = a(x-6)²
At x = 0, y = 0
Calculating a.
-12 = a*36
a = -⅓
It implies;
y-12 = -⅓(x-6)²
y = -⅓(x²-12x+36)+12
y = ⅓(-x²+12x-36+36)
y = ⅓(12x-x²)
Where y = ⅓(12x-x²) is the equation of the curve.
Calculating x when y = (32/3).
(32/3) = = ⅓(12x-x²)
32 = 12x-x²
x²-12x+32 = 0
Calculating x via completing the square approach.
(x-6)² = -32+36
x = 6±√(4)
x ≠ 6-2
x = 6+2
x = 8 units.
Calculating x when y = 0.
0 = ⅓(12x-x²)
x² = 12x
x = 12 units.
b = ½(32/3)
b = (16/3) units.
b is y coordinate.
Calculating x when y = 16/3 units.
(16/3) = ⅓(12x-x²)
x²-12x+16 = 0
Calculating x via completing the square approach.
(x-6)² = -16+36
x = 6±√(20)
x = 6±√(2√(5))
x ≠ (6+2√(5))
x = (6-2√(5)) units.
c = 4-(6-2√(5))
c = (2√(5)-2) units.
Area 2 is;
(Area under the curve at x = 4 and x = 8) - Area quadrilateral with parallel sides (16/3) units and (32/3) units respectively, and height 4 units.
⅑(416)-½((16/3)+(32/3)))*4)
⅑(416)-2(48/3)
⅑(416)-32
= ⅑(128) square units.
Area 1 is;
(Area under the curve at x = 4 and x = 12) + Area rectangle with length (16/3) units and width (2√(5)-2) units - Area 1
= ⅑(640)+((16/3)*(2√(5)-2))-⅑(128)
= ⅑(512)+⅓(32√(5)-32)
= ⅑(512+96√(5)-96)
= ⅑(416+96√(5)) square units.
Therefore;
Area 1 ÷ Area 2 in the form (a+b√(5))/c is;
⅑(416+96√(5))÷⅑(128)
= (416+96√(5))/128
= ¼(13+3√(5))
= 4.92705
We appreciate you contacting us. Our support will get back in touch with you soon!
Have a great day!
Please note that your query will be processed only if we find it relevant. Rest all requests will be ignored. If you need help with the website, please login to your dashboard and connect to support